Preparation and studying Structural and Electrical properties of nano Co3O4 - Nawar Thamer Mohammed; Wasfi Mohammed Kadem (Tikrit Journal of Pure Science, 2019)
In this study (Cobalt oxide) nano powder prepared using sol-gel method with a crystallite size 22 nm By testing XRD  and by matching with card (JCPDS) files No.( 00-042-1467). Electrical and dielectric properties like (Dielectric constant, resistivity, electrical conductivity) are studied by LCR meter with frequency range from (50 Hz) to (5 MHz ). It was noted that the resistivity and dielectric constant was decreasing while electrical conductivity increased with increased  frequency  .